Cervical tenderness (parametropathy) is a diagnostic tool for the chronic pelvic pain syndrome - Weinschenk, Stefan; Strowitzki, Thomas; Topbas Selcuki, Nura Fitnat; Zivanovic, Oliver; Gerhardt, Axel; Feißt, Manuel (Pain and therapy, 2025)
Chronic pelvic pain syndrome (CPPS) is a diagnosis of exclusion in the absence of pathological findings. We aimed to test the hypothesis that cervical motion tenderness (or parametropathy) may serve as a diagnostic tool for CPPS.